Long-term durability of alumina ceramic heads in THA - Beckmann, Nicholas A.; Gotterbarm, Tobias; Innmann, Moritz Maximilian; Merle, Christian; Bruckner, Thomas; Kretzer, Jan Philippe; Streit, Marcus R. (BMC musculoskeletal disorders, 2015)
The optimal type of bearing for hip arthroplasty remains a matter of debate. Ceramic-on-polyethylene (CoP) bearings are frequently used in younger and more active patients to reduce wear and increase biocompatibility compared to Metal-on-Polyethylene (MoP) bearings. However, in comparison to metal heads, the fracture risk of ceramic heads is higher. In addition, ceramic head fractures pose a serious complication which often necessitates major revision surgery. To date, there are no long-term data (>20 years of follow-up) reporting fracture rates of the ceramic femoral heads in CoP bearings. The purpose of this research was to investigate long-term CoP fracture rate.
Gesehen am 04.08.2020